(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: Deep parieto-occipital arteriovenous malformations (AVMs) represent a significant surgical challenge because of their complex angioarchitecture and close relationship with critical deep venous drainage pathways. Hemorrhage from these lesions further distorts normal anatomy, increasing the risk of venous injury and postoperative neurological deficits. Preservation of major medial veins, particularly the internal cerebral vein and the basal vein of Rosenthal, is essential to prevent venous infarction and ensure favorable outcomes. Case Presentation: A 24-year-old male presented with sudden severe headache, confusion, and left homonymous hemianopia. Neuroimaging revealed a right parieto-occipital intracerebral hemorrhage caused by a Spetzler-Martin Grade III AVM. Digital subtraction angiography demonstrated arterial supply from branches of the anterior, middle, and posterior cerebral arteries with deep venous drainage into the internal cerebral vein and basal vein of Rosenthal. The patient underwent urgent right parieto-occipital craniotomy. Following hematoma evacuation, meticulous microsurgical dissection allowed stepwise disconnection of arterial feeders while carefully preserving the major medial venous structures. The AVM nidus was completely excised without compromising venous drainage. Results: Postoperative CT angiography confirmed complete obliteration of the AVM with preservation of deep venous pathways. The patient showed progressive neurological recovery with improvement of visual deficits. At three months, functional status improved significantly, and by ten months follow-up the patient achieved full functional recovery without new neurological deficits. Conclusion: Microsurgical resection of deep parieto-occipital AVMs with hemorrhage can be performed safely when meticulous attention is paid to the preservation of critical medial veins. Careful operative planning, stepwise arterial disconnection, and protection of deep venous drainage are key factors for achieving complete resection and favorable neurological outcomes. Bang. J Neurosurgery 2024; 14(1): 70-73